Meyerbeer's "L'Africaine": French grand opera and the Iberian exotic - Andrews, Jean (Modern Humanities Research Association, 2007)
Meyerbeer's grand opera L'Africaine (1865) tells the story of the sixteenth-century Portuguese explorer Vasco da Gama's triumphant journey back from the east African coast and his love for an African slave. It raises questions relating to the representation of miscegenation and Iberian identity on the nineteenth-century grand opera stage.